OPERATIONAL EFFICIENCY AS A BRIDGE: ESG, GOVERNANCE, AND FINANCIAL PERFORMANCE IN STATE-OWNED ENTERPRISES - Nur Ravita Hanun; Rita Ambarwati; Faulorozi Sumartono (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study looks at how operational efficiency acts as a mediator between ESG, environmental costs, governance, and SOE financial performance in Indonesia. Method: The study used quantitative panel data from 65 SOEs’ annual, sustainability, and financial reports from 2020 to 2023. Variables cover ESG (GRI-based), CSR as environmental costs, independent commissioner proportion for GCG, and ROA for financial performance. Panel data regression analysis is performed with EViews 12 software. Results: This study shows that only ESG can improve financial performance and reduce the OEOI ratio through operational efficiency, while environmental costs and the implementation of GCG do not have a significant impact, either directly or indirectly, on financial performance. These results show the need to include embedding efficiency into ESG plans to guarantee both sustainability and profitability in state-owned companies. Novelty: This strategy emphasizes OEOI's mediation function among ESG, environmental expenses, GCG, and SOE financial performance. The OEOI ratio is presented in this study as a new mediating construct in the examination of ESG and financial performance. It closes a gap in the literature on how operational effectiveness might serve as a link between financial performance and sustainability initiatives, especially in the little-studied setting of state-owned enterprises (SOEs) in developing nations. Financial performance and operational efficiency are improved in SOEs through effective ESG integration. To avoid environmental expenses and Good Corporate Governance (GCG) becoming merely formalities without real value, so these expenditures must be strategically integrated.